Electroacupuncture-Regulated miR-34a-3p/PDCD6 Axis Promotes Post-Spinal Cord Injury Recovery in Both In Vitro and In Vivo Settings - Lili Ma; Lizhong Ma; Yu Yang; Ting Chen; Limin Wang; Qilong Deng (Journal of Immunology Research)
Electroacupuncture (EA) could enhance neuroregeneration and posttraumatic conditions; however, the underlying regulatory mechanisms remain ambiguous. PDCD6 (programmed cell death 6) is an established proapoptotic regulator which is responsible for motoneuronal death. However, its potential regulatory role in post-spinal cord injury (SCI) regeneration has remained largely unknown. Further investigations are warranted to clarify the involvement of PDCD6 post-SCI recovery and the underlying mechanisms. In our study, based on bioinformatics prediction, we found that miR-34a-3p might be an upstream regulator miRNA for PDCD6, which was subsequently validated through combined utilization of the qRT-PCR, western blot, and dual-luciferase reporter system. Our in vitro results showed that miR-34a-3p might promote the in vitro differentiation of neural stem cell (NSC) through suppressing PDCD6 and regulating other important neural markers such as fibroblast growth factor receptor 1 (FGFR1), MAP1/2 (MAP kinase kinases 1/2), myelin basic protein (MBP), βIII-tubulin Class III β-tubulin (βIII tubulin), and glial fibrillary acidic protein (GFAP). Notably, in the post-SCI rat model, exogenous miR-34a-3p agomir obviously inhibited the expression of PDCD6 at the protein level and promoted neuronal proliferation, motoneurons regeneration, and axonal myelination. The restorations at cellular level might contribute to the improved hindlimbs functions of post-SCI rats, which was manifested by the Basso-Beattie-Bresnahan (BBB) locomotor test. The impact of miR-34a-3p was further promoted by EA treatment in vivo. Conclusively, this paper argues that a miR-34a-3p/PDCD6 axis might be a candidate therapeutic target for treating SCI and that the therapeutic effect of EA is driven through this pathway.